Online consumer resilience during a pandemic: An exploratory study of e-commerce behavior before, during and after a COVID-19 lockdown. (July 2021) - Guthrie, Cameron; Fosso-Wamba, Samuel; Arnaud, Jean Brice
Abstract: The COVID-19 pandemic has disrupted retail and accelerated the trend towards electronic commerce. This study explores the reasons for and the implications of this shift. Our study builds on the consumer behavior literature, emerging COVID-19 research, and the environmentally imposed constraints perspective to describe how online purchasing behavior evolved during the COVID-19 crisis. The objective is to better understand how consumers use e-commerce to react to, cope with and adapt to periods of environmentally imposed constraints. Based on multiple sources including transaction and search data from a major French online retailer, we describe how consumer behavior evolves during such stressful life events as COVID-19. Our results support the usefulness of the multi-perspective react-cope-adapt framework of constrained consumer behavior in an online environment. Graphical abstract: Image 1